Catatan hukum pasar modal - Safitri, Indra, 1964- (Jakarta : Go Global Book, Book Pub. Div. Safitri, 1998)
On the Indonesian capital market.
Includes index.
Keywords: Capital market -- Indonesia; Capital market -- Law and legislation -- Indonesia